PENGARUH KUALITAS PELAYANAN TERHADAP LOYALITAS NASABAH DENGAN KEPUASAN SEBAGAI VARIABEL INTERVENING PADA BMT KAMPOENG SYARIAH - Taufiq Risal (Manajemen dan Bisnis, 2019)
An increase in the number of BMT Kampoeng Syariah Medan customers indicates that an increase in the number of these customers is related to customer loyalty. But the high demand for customers is not matched by an increase in service managers. So that the process of making money is experiencing a delay. The purpose of this study was to determine the effect of service quality on customer loyalty with satisfaction as an intervening variable. The population used is customers who use BMT Kampoeng Syariah Medan landline services. Based on the results of this study indicate (1) the first hypothesis of the service quality variable (X) to the satisfaction variable (Z) shows that service quality has a positive and significant effect on satisfaction; (2) the similarity hypothesis of the three service quality variables (X) and customer satisfaction with customer loyalty variables (Y) shows that service quality and customer satisfaction have a positive and significant effect on customer loyalty. In testing the direct and indirect effects, the service quality variable (X) on customer loyalty (Y) through satisfaction (Z) shows that satisfaction can mediate the relationship between service quality on customer loyalty with positive results Keywords customer loyalty, customer satisfaction, service quality